Sistem Informasi Geografis Wisata Religi Berbasis Web Mobile - Vinandari, Nur; Hafizd, Khairul Anwar; Noor, Muhammad (Teknik Informatika, Politeknik Negeri Tanah Laut, 2019)
Tanah Laut is one of the mainstays of the tourist sector in South Kalimantan. Tanah Laut Regency has tourism potential, one of which is religious tourism. Religious tourism is a tourist activity to get fun or entertainment, also will get lessons about Islamic teachings and increase knowledge. The government of Tanah Laut regency conducting tourism promotions still through mass media such as newspapers and pamphlet methods is not enough to support tourist attractions for tourists. And there is no specific information system on religious tourism and besides that in the Tourism Office the data on religious tourism in several sub-districts in the regency of the sea are still not yet complete or complete in the data collection of religious tourism spots. The purpose of the research is to make a design and a Geographic Tourism Information System that can display a picture and provide detailed information on the location of religious tourism in several sub-districts in Tanah Laut district. Information in the form of a web mobile is expected to help the community to access it anywhere and anytime. In geographical information systems, religious tourism is built using the Hypertext Preprocessor (PHP) and JavaScript programming languages.